PENERAPAN SISTEM AKUNTANSI PADA UMKM MAKANAN RINGAN DI KABUPATEN TULUNGAGUNG - Sofi Dwi Ayu Cahyani (Universitas Tulungagung, 2024)
Abstract Using the descriptive analytic methodology, this study endeavors to ascertain the extent to which accounting documentation is executed in accordance with the financial accounting standards mandated for organizations, particularly focusing on micro, small, and medium enterprises, within the geographic confines of the Tulungagung region. The descriptive analysis methodology serves to initially elucidate the landscape of small and medium enterprises in the Tulungagung district. The study's conclusions show that small and medium-sized businesses in Tulungagung Regency, which are the study's subjects, are not predominantly utilizing established accounting recording methodologies, thereby suggesting that these enterprises have not fully embraced the requisite accounting record-keeping practices. This situation is attributed to the constraints posed by limited human resources coupled with insufficient accounting competencies or knowledge. The execution of the accounting recording system undertaken by UD Hikmah in Tulungagung City represents merely a fraction of the comprehensive accounting recording system. This phenomenon can be attributed to the insufficient understanding possessed by business proprietors regarding the formulation of intricate financial reports. Consequently, the proprietor of UD Hikmah is unable to ascertain the precise magnitude of profit generated. Abstrak Studi ini bertujuan untuk memberikan penjelasan tentang penggunaan catatan akuntansi yang sesuai dengan standar akuntansi keuangan untuk perusahaan mikro, kecil, dan menengah di Kabupaten Tulungagung. Metodologi analisis deskriptif digunakan dalam mencapai tujuan ini. Metode analisis deskriptif digunakan sebagai dasar untuk memahami karakteristik bisnis kecil dan menengah di Kabupaten Tulungagung. Hasil studi menunjukkan bahwa subjek investigasi di Kabupaten Tulungagung, khususnya usaha kecil dan menengah, tidak secara dominan menggunakan metode pencatatan akuntansi yang komprehensif, sehingga menunjukkan bahwa entitas tersebut belum mengadopsi praktik akuntansi yang diperlukan secara memadai. Ketidakmampuan ini dapat dikaitkan dengan kelangkaan sumber daya manusia ditambah dengan defisit dalam kemahiran atau pengetahuan akuntansi. Praktik pencatatan akuntansi yang dilaksanakan oleh UD Hikmah di Kota Tulungagung hanya mewakili aspek minimal dari keseluruhan kerangka pencatatan akuntansi. Keterbatasan ini muncul dari kurangnya pemahaman pemilik usaha tentang penyusunan laporan keuangan secara rinci, yang akibatnya telah mengakibatkan ketidakmampuan pemilik UD Hikmah untuk memastikan angka laba yang tepat.